Correlations of chlamydia and gonorrhoea among pharyngeal, rectal and urethral sites among Thai men who have sex with men: multicentre community-led test and treat cohort in Thailand. Issue 6 (27th June 2019) - Hiransuthikul, Akarin; Sungsing, Thanthip; Jantarapakde, Jureeporn; Trachunthong, Deondara; Mills, Stephen; Vannakit, Ravipa; Phanuphak, Praphan; Phanuphak, Nittaya
Abstract : Objective: Routine screening for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections in sexually exposed anatomical sites may be challenging in resource-limited settings. The objective of this study was to determine the proportion of missed CT/NG diagnoses if a single anatomical site screening was performed among men who have sex with men (MSM) by examining the pattern of anatomical sites of CT/NG infections. Methods: Thai MSM were enrolled to the community-led test and treat cohort. Screening for CT/NG infections was performed from pharyngeal swab, rectal swab and urine using nucleic acid amplification testing. The correlations of CT/NG among the three anatomical sites were analysed. Results: Among 1610 MSM included in the analysis, 21.7% had CT and 15.5% had NG infection at any anatomical site. Among those tested negative for CT or NG infection at either pharyngeal, rectal or urethral site, 8%–19% had CT infection and 7%–12% had NG infection at the remaining two sites. Of the total 349 CT infections, 85.9%, 30.6% and 67.8% would have been missed if only pharyngeal, rectal or urethral screening was performed, respectively. Of the total 249 NG infection, 55.7%, 39.6% and 77.4% would have been missed if only pharyngeal, rectal or urethral screening was performed, respectively. The majority of each anatomical site of CT/NG infection was isolated to their respective site, with rectal site having the highest proportion of isolation: 78.9% of rectal CT and 62.7% of rectal NG infection. Conclusions: A high proportion of CT/NG infections would be missed if single anatomical site screening was performed among MSM. All-site screening is highly recommended, but if not feasible, rectal screening provides the highest yield of CT/NG diagnoses. Effort in lowering the cost of the CT/NG screening test or developing affordable molecular technologies for CT/NG detection is needed for MSM in resource-limited settings. Trial Registration Number: NCT03580512 ; Results.